Naftopidil for the treatment of benign prostate hyperplasia: a systematic review. (April 2014) - Castiglione, Fabio; Benigni, Fabio; Briganti, Alberto; Salonia, Andrea; Villa, Luca; Nini, Alessandro; Di Trapani, Ettore; Capitanio, Umberto; Hedlund, Petter; Montorsi, Francesco
Abstract Objectives: The aim of the study was to systematically review the effects of the adrenoreceptor A1D antagonist naftopidil in the management of lower urinary tract symptoms (LUTS). Methods: A structured and comprehensive MEDLINE search was conducted for original articles, reviews, and metanalyses assessing the clinical pharmacology as well as the safety of naftopidil in the treatment of LUTS secondary to BPH. English-language publications dating from 1950 to 2013 were considered. Results: In the considered timeframe, 14 randomized clinical trials (RCT) were reported. Overall, the outcome measures assessed in the various reports included in the present review were changes from baseline in: International Prostate Symptom Score (IPSS), quality of life (QoL) score, maximum urinary flow rate (Qmax), residual volume (PVR), and adverse effects. Although additional well designed, worldwide, placebo-controlled and randomized studies are necessary to confirm the long-term outcomes of naftopidil pharmacotherapy, current data suggest that naftopidil administration in BPH patients provides comparable improvements in total IPSS, QoL, and urinary symptoms from baseline relative to 0.2 mg/d tamsulosin and 8 mg/d silodosin. However, improvements in Qmax are generally less with naftopidil than with tamsulosin. Reported adverse effects related to naftopidil administration are negligible and usually mild. Conclusion: It remains unknown whether the data reported on naftopidil in the Japanese population are applicable in symptomatic BPH patients from western countries given that: (1) no English-language clinical trials have compared naftopidil to placebo in Western countries; (2) all clinical trials available were carried out in Japan; (3) in the comparative studies with tamsulosin, the dose of this drug was lower than the recommended dose in Western countries; (4) no data from long-term clinical trials evaluating drug safety beyond 18 weeks.